Tetrathionate hydrolase from the acidophilic microorganisms - Kanao, Tadayoshi (Frontiers in Microbiology, 2024)
Tetrathionate hydrolase (TTH) is a unique enzyme found in acidophilic sulfur-oxidizing microorganisms, such as bacteria and archaea. This enzyme catalyzes the hydrolysis of tetrathionate to thiosulfate, elemental sulfur, and sulfate. It is also involved in dissimilatory sulfur oxidation metabolism, the S4-intermediate pathway. TTHs have been purified and characterized from acidophilic autotrophic sulfur-oxidizing microorganisms. All purified TTHs show an optimum pH in the acidic range, suggesting that they are localized in the periplasmic space or outer membrane. In particular, the gene encoding TTH from Acidithiobacillus ferrooxidans (Af-tth) was identified and recombinantly expressed in Escherichia coli cells. TTH activity could be recovered from the recombinant inclusion bodies by acid refolding treatment for crystallization. The mechanism of tetrathionate hydrolysis was then elucidated by X-ray crystal structure analysis. Af-tth is highly expressed in tetrathionate-grown cells but not in iron-grown cells. These unique structural properties, reaction mechanisms, gene expression, and regulatory mechanisms are discussed in this review.